2021
DOI: 10.1186/s13068-020-01858-x
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR of unlabeled plant cell walls: high-resolution structural analysis without isotopic enrichment

Abstract: Background Multidimensional solid-state nuclear magnetic resonance (ssNMR) spectroscopy has emerged as an indispensable technique for resolving polymer structure and intermolecular packing in primary and secondary plant cell walls. Isotope (13C) enrichment provides feasible sensitivity for measuring 2D/3D correlation spectra, but this time-consuming procedure and its associated expenses have restricted the application of ssNMR in lignocellulose analysis. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 69 publications
3
33
0
Order By: Relevance
“…DNP analysis has been applied to various carbohydrate and plant systems using different protocols 75 77 . Recently, we have demonstrated that the radical can effectively and homogeneously polarize all molecules in cell wall materials 78 . Lignin had a slightly shorter DNP buildup time (1.8 s) compared with polysaccharides (2.2 s).…”
Section: Methodsmentioning
confidence: 99%
“…DNP analysis has been applied to various carbohydrate and plant systems using different protocols 75 77 . Recently, we have demonstrated that the radical can effectively and homogeneously polarize all molecules in cell wall materials 78 . Lignin had a slightly shorter DNP buildup time (1.8 s) compared with polysaccharides (2.2 s).…”
Section: Methodsmentioning
confidence: 99%
“…At first, this 2D experiment was considered impossible to achieve, because there is a low natural abundance of 13 C (1.1%) and a lower probability of detecting a cross peak between two carbons. However, now this experiment can be completed using DNP system within 35 h [77]. In cellulose, eight types of glucose units appear: (a) a-e for the glucan chains found in the core of the microfibrils, and (b) f-h for those on the surface.…”
Section: Cellulose Polymorphism In Plant Primary Cell Wallsmentioning
confidence: 99%
“…MAS-DNP is efficient for the detection of ordered molecules, such as cellulose carbons and part of xylan backbones, but does not detect arabinose sidechains. This is a result of the wide distribution of conformations of these mobile molecules, resulting in a broadening of their signals [77].…”
Section: Lignocellulosic Biomass Structure Interpretationmentioning
confidence: 99%
“…Metabolomics is also of great interest for food quantification, including molecular based traceability and nutritional value [20,[52][53][54][55][56][57][58]. It was applied for the generation of metabolic markers between two species used as sources of goji berries, such as Lycium barbarum L. and Lycium chinense Mill., which are very similar red ovoid fruits and difficult to discriminate with morphological or molecular markers [20].…”
Section: Nutritional Cropsmentioning
confidence: 99%
“…The multi-dimensional solid-state NMR metabolomics has been applied to lignin, cellulose, and hemicellulose quantification through direct measurement without chemical or enzymatic pre-treatment [ 57 ]. Using solid-state NMR spectroscopy revealed increased biosynthesis of cellulose and xylan in O. sativa mutants compared to the wild type [ 58 ].…”
Section: Metabolic Profiling Of Nutritional Crops and Medicinal Plantsmentioning
confidence: 99%